(untitled) (Indian Journal of Animal Production and Management, 2025)
Present study was conducted to identify various constraints perceived by SDAH Personnel in delivering the livestock extension services in central plain zone of Uttar Pradesh. An ex-post facto and exploratory research design were used to study the perceived constraints in four districts of Uttar Pradesh. A total 16 indicators of constraints were selected through previous studies and experts opinion. Data were collected by personal interview from 120 (60 Veterinary Officer and 60 Livestock Extension Officers) State Department of Animal Husbandry personnel randomly selected from available list at the district head quarter. The study revealed that, livestock extension activities suffer due to inadequate veterinary staff and this is the most severe constraint followed by inadequate budget allotment and over burdening of other paper work with respective ranks I, II and III. Recruitment of more number women SDAH personnel, organizing women targeted livestock extension activities, establishing separate grassroot level livestock extension wing were the major common suggestion revealed by the Veterinary Officers and the Livestock Extension Officers.